Comprehensive Analysis of Regulatory Factors and Immune-Associated Patterns to Decipher Common and BRCA1/2 Mutation-Type-Specific Critical Regulation in Breast Cancer - Li, Yue; Dong, Wei; Zhang, Pengqian; Zhang, Ting; Ma, Ling; Qu, Meng; Ma, Xingcong; Zhou, Xiaoyan; He, Qian (Frontiers in Cell and Developmental Biology, 2021)
Background BRCA1/2 mutations are closely related to high lifetime risk of breast cancer (BC). The objective of this study was to identify the genes, regulators, and immune-associated patterns underlying disease pathology in patients with BRCA mutations and their associations with clinical traits. Methods RNA sequencing data and clinical information from The Cancer Genome Atlas (TCGA; N=36 BRCA1-mutant BC samples; N=49 BRCA2-mutant BC samples; and N=117 BRCA1/2-wild-type BC samples) were used for discovery, which included consensus network analysis, function enrichment, and identification and analysis of hub genes; other TCGA data (N=117 triple-negative BC samples) and two Gene Expression Omnibus database expression profiles were used as validation cohorts. Results Consensus network analysis helped to identify specific co-expressed clinical modules that showed positive correlations with tumor stage, number of positive lymph nodes, and margin status in BRCA1/2-mutant BC but had no significant correlations in BRCA1/2-wild-type BC. Functional enrichment analysis suggested potential mechanisms in BRCA1/2 carriers that could regulate the cell cycle, immune response, cellular metabolic processes, and cell migration and thus influence metastasis and prognosis, via pathways including p53 and JAK–STAT signaling. Consensus network analysis identified the specific and common carcinogenic mechanisms involving BRCA mutations. Intermodular network analysis showed significant enrichment of the E2F transcription factor family associated with cell cycle regulation and the IRF family associated with immune response regulation. Eight hub genes, including ISG15, BUB1, and TTK, were upregulated in several BRCA1/2-mutant BC datasets and showed prognostic value in BC. Furthermore, their genetic expression was related to higher levels of immune infiltration in BRCA1/2-mutant BC, which manifested as recruitment of T helper cells (Th1 cells), follicular helper T cells (Tfh), and regulatory T cells, and T cell exhaustion. Moreover, important indicators for evaluation of BC immunotherapy, tumor mutational burden, and neoantigen load were positively associated with expression of some hub genes. Conclusions We constructed a BRCA1/2 mutation-type-specific co-expressed gene network with related transcription factors and immune-associated patterns to reflect common and specific patterns of tumor metastasis and tumor immune microenvironment regulation, providing novel insights into the pathological process of this disease and the corresponding BRCA mutations.